Management of gastrosplenic fistula in the emergency setting - A case report and review of the literature. (May 2018) - Frenkel, Amit; Bichovsky, Yoav; Perry, Zvi H.; Peiser, Jochanan; Roy-Shapira, Aviel; Brotfain, Evgeni; Koyfman, Leonid; Binyamin, Yair; Nalbandyan, Karen; Klein, Moti
Abstract: Introduction: A gastrosplenic fistula (GSF) is a very rare complication that arises mainly from a splenic or gastric large cell lymphoma. The proximity of the gastric fundus to the enlarged fragile spleen may facilitate the fistulisation. This complication can lead to massive bleeding, which, though uncommon, may be lethal. We present a patient with massive upper gastrointestinal bleeding secondary to a GSF. Case presentation: We present a 48-year-old man with a refractory diffuse large B-cell lymphoma who was admitted to our hospital due to hematemesis. On arrival, he was in hemorrhagic shock, and was taken directly to the intensive care unit. The source of bleeding could not be identified on gastroscopy, the patient remained hemodynamically unstable and a laparotomy was performed. A fistula between a branch of the splenic artery and the stomach was identified. The stomach appeared to be involved in the malignant process. After subtotal gastrectomy and splenectomy, the bleeding was controlled. After stabilization, the patient was admitted to the intensive care unit, and 24 hours later was discharged in stable condition. Discussion: We describe a fistula between a branch of the splenic artery and the stomach, which was accompanied by massive bleeding. An emergency laparotomy saved the patient's life. Conclusion: The purpose of this report is to alert physicians that surgical intervention can be lifesaving in this rare malignant condition. A literature review focusing on the presenting symptoms and the epidemiology of GSF is presented. Highlights: A review showed that 75% of gastrosplenic fistulae were associated with lymphoma and 57% were of large B cell type. Massive bleeding in the current case is uncommon for gastrosplenic fistulas. For gastrosplenic fistulas with massive bleeding, prompt surgery offers a good chance of survival.